We will not return home - Salimian, Salah; Azami, Arash; Maeroufnezhad, Ali (Kalágatos, 2025)
This article is a test and another approach to freedom that, through the lens of Jacques Derrida, is liberated by being situated under the concept of graphe and by freeing itself from the constraints of any signifier, embarking on an unfinished journey. The intention is not to postpone freedom to a state of absence, but rather, if possible, to liberate freedom from any determinate meaning and from the constraints of any signified.